Classroom learning environment as a determinant of psychological well-being in adolescents - Yicen Meng; Nik Rosila Nik Yaacob; Yasmin Othman Mydin (International Journal of Evaluation and Research in Education (IJERE), 2026)
Psychological well-being (PWB) is critical in adolescent development as well as academic success. In terms of self-determination theory, satisfaction of autonomy, competence, and relatedness psychological needs leads to PWB. In schooling contexts, these psychological needs can be satisfied in a supportive classroom learning environment (CLE), which in turn will promote adolescents’ overall well-being. The study examines the predictive impact of CLE on Chinese adolescent PWB as well as which specific dimensions of CLE are effective predictors to PWB. A sample consisting of 918 14- to 19-year-old adolescents participated. What Is Happening In this Class (WIHIC) questionnaire and the Brief Chinese Version of the psychological well-being scale (PWBS) were applied for data collection. Pearson correlation showed a positive correlation between CLE’s seven dimensions and PWB. Meanwhile, structural equation modelling (SEM) analysis identified student cohesiveness, teacher support, involvement, and task orientation, dimensions of CLE, significantly predict PWB. The result indicated CLE plays a crucial role in predicting PWB. The findings inform recommendations for improving adolescents’ PWB and discusses further implications.